INTEGRATED DINIYAH AND FORMAL CURRICULUM MANAGEMENT SYSTEM AT SUNAN DRAJAT ISLAMIC BOARDING SCHOOL - Hasyim Rosyidi; Muhammad Nur Musabbih Musabbih (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study examines the integrative curriculum management system that combines diniyah and formal education at the Sunan Drajat Islamic Boarding School. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving members of the Majelis Ilmu (Science Council), educators, and students. The results show that curriculum planning is systematically implemented through a professional Majelis Ilmu (Science Council) consisting of 12 experts, using Focus Group Discussion mechanisms and needs analysis. The organization applies a dual-track structure with the Santri Affairs Division managing the diniyah curriculum and the Formal Division managing the general curriculum, coordinated through the Consultative Assembly. Implementation follows centralized command from the foundation with a phased approach from adapting national standards to pure pesantren products. Evaluation is carried out periodically through monthly reporting using the CIPP model with a single integrated report card format. Key challenges include teacher readiness, duplication of materials, and students' cognitive load, which are addressed through continuous coaching, differentiated material distribution, expert-based governance, and a balanced curriculum approach. The study contributes empirical documentation of deliberative curriculum development in the pesantren context, indigenous knowledge development, and a tri-dimensional holistic evaluation system that integrates religious and academic assessments